Integrating Claim, Evidence, Reasoning into a Four-Tier Diagnostic Test to Assess Students’ Conceptual Understanding of Work and Energy - Muhammad Fatikhul Alam Bima Sakti; Sunyoto Eko Nugroho; Budi Naini Mindyarto (Physics Communication, 2026)
This study reports the development and validation of a Four-Tier Diagnostic Test integrated with the Claim, Evidence, and Reasoning (CER) framework to examine senior high school students’ conceptual understanding of work and energy. Although four-tier diagnostics and CER have been widely implemented independently, limited research has combined both approaches within a unified diagnostic assessment framework. The integration is intended to capture students’ answer accuracy, confidence level, and the structure of their scientific reasoning simultaneously. Using a Research and Development design, five CER-based four-tier items were developed and administered to 100 twelfthgrade students. Content and construct validity were established through expert review, and reliability was examined using Cronbach’s Alpha. Misconceptions were analysed using the Confidence Discrimination Quotient (CDQ) and fourtier interpretation criteria. The findings indicate that misconception rates ranged from 23% to 25%, while CDQ values varied between −0.006 and 0.024, suggesting the presence of moderate conceptual uncertainty. Most items demonstrated high difficulty levels and moderate discrimination indices, indicating that work–energy concepts remain cognitively demanding. The integration of CER into the four-tier structure provided richer diagnostic information by linking correctness, reasoning quality, and confidence level. These results highlight the potential of CER-integrated diagnostic assessment in identifying nuanced misconceptions in physics learning.